Ornithine decarboxylase inhibition downregulates multiple pathways involved in the formation of precancerous lesions of esophageal squamous cell cancer. Issue 2 (3rd December 2019) - Xie, Yifei; Dong, Christopher D; Wu, Qiong; Jiang, Yanan; Yao, Ke; Zhang, Jing; Zhao, Simin; Ren, Ying; Yuan, Qiang; Chen, Xinhuan; Liu, Zhongyi; Zhao, Jimin; et al.
Abstract: The high incidence and mortality of esophageal squamous cell cancer (ESCC) is a major health problem worldwide. Precancerous lesions of ESCC may either progress to cancer or revert to normal epithelium with appropriate interventions; the bidirectional instability of the precancerous lesions of ESCC provides opportunities for intervention. Reports suggest that the upregulation of ornithine decarboxylase (ODC) is closely related to carcinogenesis. In this study, we investigated whether ODC may act as a target for chemoprevention in ESCC. Immunohistochemistry (IHC) assays indicate that ODC expression is higher in esophageal precancerous lesions compared with normal tissue controls. Its overexpression promotes cell proliferation and transformation of normal esophageal epithelial cells, and its activity is increased after N ‐nitrosomethylbenzylamine (NMBA) induction in Shantou human embryonic esophageal cell line (SHEE) and human immortalized cells (Het1A) cells. In addition, p38 α, extracellular regulated kinase (ERK1/2) in the mitogen‐activated protein kinase pathway and protein kinase B (AKT)/mammalian target of rapamycin (mTOR)/ribosomal protein S6 kinase (p70S6K) pathways are activated in response to NMBA treatment. Difluoromethylornithine (DFMO) is an ODC inhibitor, which inhibits NMBA‐induced activation of p38 α, ERK1/2 and AKT/mTOR/p70S6K pathways; this has been verified by Western blotting. DFMO was also found to suppress the development of esophageal precancerous lesions in an NMBA‐induced rat model; IHC demonstrated p38 α, ERK1/2, and AKT/mTOR/p70S6K pathways to be downregulated in these rats. These findings indicate the mechanisms by which ODC inhibition suppresses the development of esophageal precancerous lesions by downregulating p38 α, ERK1/2, and AKT/mTOR/p70S6k signaling pathways, ODC may be a potential target for chemoprevention in ESCC.